The Kantian ideals and the Mongolian young democracy: Achieving peace and democracy through international cooperation (Кантын үзэл санаа ба Монголын залуу ардчилал: олон улсын хамтын ажиллагаагаар энх тайван ба ардчилалд хүрэх замд) - Т, ЗАЯА. (Politology, 2023)
The purpose of this article is to demonstrate how, even in the most remote from Europe country, in this case in Mongolia, the ideas of such great philosophers as Rousseau, Montesquieu and Kant went to this ancient nation to transform it entirely from a communist state to a vibrant democracy.